Sejarah dalam Membentuk Era Modern: Studi Kasus Invasi Ukraina oleh Rusia - Audrey Chairunnisa; Diva Firyal Athaaya (CV. Ulil Albab Corp, 2022)
Regardless of the current conflict that is happening, ethnically, both Russia and Ukraine share the same motherhood; they come from Rus and Kievan Rus. The bond they have also come from the Union of Soviet Socialist Republic which both of them also have the same culture, but not until the Russian empire conducted a regulation that is called Russification. This means they want to Russia-fy all of the Ukrainian and Belarusian ethnics by erasing their identity and culture. Thus, this law also forbids them to use the Ukrainian language and foremost, forcing them to change their belief into Russian Orthodoxy.